Spinal muscular atrophy with severe scoliosis: a case report - Dikahayu Alifia Anugrah; Sunartini Sunartini; Mohammad Juffrie (Paediatrica Indonesiana, 2023)
Spinal muscular atrophy (SMA) is an autosomal recessive neurodegenerative disease that causes general weakness, muscle atrophy, and poor muscle movement. This condition is due to a homozygous disruption of the survival motor neuron (SMN) 1 survival gene due to deletion, conversion, or mutation.1